Implementasi Integrasi Kurikulum Cambridge dengan Kurikulum Nasional di SMP Islamic International School PSM Magetan - Zainal Arifin (Excelencia: Journal of Islamic Education & Management, 2024)
Implementation of the curriculum in an educational institution cannot be separated from curriculum planning because good curriculum planning will facilitate all activities from organizing, implementing and evaluating learning in schools and as a reference for achieving the vision, mission and goals of education. This research uses a type of qualitative research and uses a case study approach. The data obtained in this study are in the form of words from interviews and in the form of actions from observations. As for the source of data from interviews, data regarding actions obtained from observations, and other data sources from documents from the results of documentation. The results of this study explain the integration planning of the Cambridge curriculum with the national curriculum, so that in planning the curriculum in the learning process it is designed in the form of a syllabus and learning implementation plans that refer to content standards. The implementation of learning applies the integration of the National Curriculum and the Cambridge International Curriculum and also uses the Islamic curriculum. However, the implementation uses the National curriculum which is inserted with the Cambridge international curriculum. Organizing the curriculum in schools includes organizing subjects, organizing learning, organizing teaching loads and learning systems. components of content and organization of teaching materials, components of teaching and learning patterns and strategies, and evaluation components. The implications of implementing curriculum integration include changes in students' attitudes both in terms of spiritual values, social values, cognitive values ​​and psychomotor values.